Anti‐Inflammatory Phomalones from the Deep‐Sea‐Derived Fungus Trichobotrys effuse FS522 - Huang, Hui‐Bin; Chen, Yu‐Chan; Wen, Ting‐Yue; Li, Sai‐Ni; Liu, Zhao‐Ming; Zhang, Wei‐Min; Gao, Xiao‐Xia (Chemistry & biodiversity, 2023)
Four new phomalones A−D (1–4), together with five known analogues (5–9) were isolated from the deep‐sea‐derived fungus Trichobotrys effuse FS522. Their structures of the new compounds established by analysis of their NMR and HR‐ESI‐MS spectroscopic data, and the absolute configurations of 2 was determined by electronic circular dichroism (ECD) calculations. compounds 4, 6 and 8 substantially inhibited the production of nitric oxide (NO) with IC50 values of 4.64, 13.90, and 34.07 μM.